An Optimum Shift-and-Weighted brightness mapping for low-illumination image restoration. (19th May 2019) - Peng, Yeping; Shi, Haiyan; Wu, Hongkun; Li, Ruowei; Kwok, Ngaiming; Liu, San Chi; Liu, Shilong; Rahnam, Md Arifur
ABSTRACT: Images captured under low-illumination environments often impose difficulties in revealing objects of interest. An effective approach, Optimum Shift-and-Weighted Brightness Mapping, is here proposed that can optimally enhance the image for higher brightness, information content, and colour vividness. Specifically, the input-output brightness mapping is determined by a shifted spline curve and a larger amplification is allowed for low-brightness pixels. A weighting function is further applied such that high brightness pixels are preserved. The final enhanced image is obtained by inserting the extracted high frequency components from the original input to the brightness boosted image. The algorithm is adaptive to image contents where parameters are optimized using the efficient golden section search instead of relying on user specified coefficients. Experimental results, from a large set of test images, showed that better quality images could be obtained on a variety of low-illumination scenarios as compared to several recent approaches.